Kajian Potensi Penyerapan Karbon Dioksida (CO2) Hutan Sekitar Longsor di Sepanjang Tol Trans Palopo-Toraja - Witno Witno; Maria Maria; Liana Liana; Wardi Wardi (Jurnal Ilmu Kehutanan, 2024)
Forests are crucial in absorbing carbon dioxide (CO2) from the atmosphere through photosynthesis and storing the carbon in its biomass. This research aimed to assess the potential for CO2 absorption of forests around landslides along the Trans Palopo-Toraja highways. This research employed a destructive sampling to measure understorey and litter biomass. Furthermore, it measured the biomass of understorey plants and litter with a destructive method. The 12 measurement plots were purposively placed on the landslide points to represent various vegetation conditions. The results revealed the presence of 77 plant species, totaling 554 individuals on the measurement plots. Plot 4 and Plot 1 showed the highest and lowest carbon absorption potential at 790.39 tons/ha and 199.63 tons/ha, respectively. The estimated average absorption of 12 plots was 461.75 tons/ha. Tree-level vegetation had the highest carbon absorption value due to its bigger diameter and CO2 absorption capacity than saplings and poles.